Coach ratings of skills and their relations to practice, play and successful transitions from youth-elite to adult-professional status in soccer. Issue 17 (2nd September 2018) - Hendry, David T; Williams, A. Mark; Hodges, Nicola J
ABSTRACT: Elite soccer players (~15 yr) from professional academies in the UK were rated on technical, tactical, physical and creative skills by coaches at time 1 (T1). Players estimated accumulated hours in soccer practice (coach-led activities) and play (self-led activities) during childhood. Coach-ratings were again collected 2.5 yr later (T2) for players that received a professional contract (~17 yr). Adult-professional status was determined at T3 (~ 20 yr). Skill ratings distinguished across the three "future" groups (academy-only, youth-professional only and adult-professional), for all but creative skill. For players that transitioned to youth-professional, medium sized correlations were noted between childhood practice amounts and technical and creative skill ratings at T1, although practice amounts correlated more strongly with skill ratings at T2. Play amounts were not related to any skills. Within groups of youth elite athletes, domain-specific play in childhood, and to a lesser degree practice, were generally not good discriminators of specific-skills. The effects of sport-specific practice on the development (and discriminability) of skills takes time to emerge. We consider the implications for talent development models and purported links between play and creativity.